Integrated timetable system for class scheduling and resource management - Yap, Zhong Yew (2025)
Due to the growing complexity of scheduling courses at the university, the necessity for a quality and user comfortable scheduling system has emerged. It is very difficult to take advantage of surplus resources fully and allocate them effectively without affecting normal activities and constraints [13]. For students to be able to easily book courses, check timetables, and manage their resources better, the project proposes developing an integrated timetable system. The system allows students to arrange for classes, check the availability of teachers, view their schedules, and track changes or cancellations of lessons in real time. It gives students also complete information on the rooms where the classes and courses are taking place, including maps of the campus for classes. Thanks to the real-time information available about the schedules of lecturers and the changes for classes, students are alerted immediately whenever there are changes in the planned meeting times. Moreover, the application includes features which empower the management to control class schedules, teachers and classrooms combination to form a complete solution for students and staff members. The central aim of the system being proposed is that it will automate and centralize the designing process to reduce the incidence of scheduling conflicts, enhance resource allocation and improve learning experience for the educators and the learners.